(untitled) (Contemporary Mathematics, 2024)
Among other things, finding solutions for functional as well as other types of problems (including differential and integral) by suggesting fixed-point procedures is a difficult task, especially when we study the approximation techniques in the absence of linearity in the domain of definition. In this paper, an effective iterative approximation procedure is successfully applied to find fixed points of a general class of operators in the nonlinear setting of CAT(0) spaces. The results are illustrated with the help of some examples. Some numerical computations are also provided. Eventually, we prove that our new results are applicable to solving split feasibility problems. Our results are new and complement some recently published results from the literature.